Assessment of Regional Ventilation During Recruitment Maneuver by Electrical Impedance Tomography in Dogs - Ambrósio, Aline Magalhães; Sanchez, Ana Flávia; Pereira, Marco Aurélio Amador; Andrade, Felipe Silveira Rego Monteiro De; Rodrigues, Renata Ramos; Vitorasso, Renato de Lima; Moriya, Henrique Takachi; Fantoni, Denise Tabacchi (Frontiers in Veterinary Science, 2022)
Background: During protective mechanical ventilation, the electrical impedance tomography has been used to monitor alveolar recruitment maneuvers as well as the distribution of regional ventilation. This technique can infer atelectasis and lung overdistention during mechanical ventilation in anesthetized patients or in the ICU. Changes in lung tissue stretching are evaluated by monitoring the electrical impedance of lung tissue with each respiratory cycle. Objective: This study aimed to evaluate the distribution of regional ventilation during recruitment maneuver based on the variables obtained in pulmonary electrical impedance tomography, during protective mechanical ventilation, focusing on better lung recruitment associated with less or no overdistention. Methods: Prospective clinical study using seven adults client-owned healthy dogs, weighing 25 ± 6 kg, undergoing elective ovariohysterectomy or orchiectomy. The animals were anesthetized and ventilated in volume-controlled mode (7ml.kg-1) with stepwise PEEP increases from 0 to 20 cmH2O in steps of 5 cmH2O every 5 minutes and then a stepwise decrease. EIT, respiratory mechanics, oxygenation, and hemodynamic variables were recorded for each PEEP step. Results: The results showed that the regional compliance of the dependent lung significantly increased in PEEP 10 cmH2O decrease step when compared to baseline (p < 0.027) and for the non-dependent lung there was a decrease in compliance at PEEP 20 cmH2O (p = 0.039) compared to baseline. A higher level of PEEP was associated with a significant increase in silent space of the non-dependent regions from PEEP 10 cmH2O increase step (p = 0.048) until PEEP 15 cmH2O (0.019) decrease step with the highest values in PEEP 20 cmH20 (p = 0.016) returning to baseline values thereafter. Silent space of the dependent regions did not show any significant changes. Drive pressure decreased significantly in PEEP 10 and 5 cmH2O decrease step (p = 0.032) accompanied by increased respiratory static compliance in the same PEEP step (p = 0.035 and 0.018 respectively). Conclusions: The regional ventilation distribution assessed by EIT showed that the best PEEP value for recruitment maintenance, capable of decreasing areas of pulmonary atelectasis independent regions promoting less overinflation in non-dependent areas was from 10 to 5 cmH2O decreased step.